Pengaruh Perencanaan Anggaran, Pelaksanaan Anggaran, Regulasi, Komitmen Organisasi Terhadap Kinerja Instansi Daerah Banyuasin - Tio Saputra; Sarikadarwati; Edwin Frymaruwah (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to examine the influence of budget planning, budget implementation, regulations, and organizational commitment on the performance of regional government agencies in Banyuasin Regency. Method: This research employed a quantitative approach. Data were collected through questionnaires distributed to employees involved in budget management within 32 Regional Government Organizations (OPD) in Banyuasin Regency. The population consisted of budget management officials, including Budget Users (PA), Budget User Authorities (KPA), Technical Activity Implementation Officers (PPTK), Financial Administration Officers (PPK), and Expenditure Treasurers. A purposive sampling technique was used, resulting in a sample of 160 respondents. Data were analyzed using multiple linear regression analysis with the assistance of IBM SPSS Statistics. Finding: The results indicate that budget planning, budget implementation, regulations, and organizational commitment have a positive and significant effect on the performance of regional government agencies. Simultaneously, all independent variables significantly influence regional agency performance, indicating that effective budget management and strong organizational commitment contribute to improved organizational performance. Novelty: This study contributes to the public sector accounting literature by developing an integrated model that simultaneously examines budget planning, budget implementation, regulations, and organizational commitment as determinants of regional government agency performance. Unlike previous studies that generally focus on one or two aspects of budget management, this research combines managerial, regulatory, and behavioral factors within a single framework and provides empirical evidence from regional government organizations in Banyuasin Regency. The findings offer a more comprehensive understanding of how budget governance and organizational commitment interact to improve public sector performance.